THE PLANNING FOR UPPER SHOES RAW MATERIAL INVENTORY USING THE MATERIAL REQUIREMENT PLANNING (MRP) METHOD (Case Study : PT X) - Apriliza, Poppy; Supian, Sudradjat; Nahar, Julita (International Journal of Global Operations Research, 2023)
The planning of raw material inventory is one of the essential factors in planning the order of the raw materials that can make a company maintain its production quality. The company’s policies can be implemented in various ways, such as in planning the raw materials inventory to avoid shortages and excesses of the raw materials supply. However, X Inc. has not implemented inventory planning properly, making the costs incurred by the company not optimal. Thus, Material Requirement Planning (MRP) will be used to determine the scheduling time and quantity of raw materials for ordering with lot sizing techniques. Lot sizing techniques provide solutions to determine the right quantity of raw material orders and minimum total inventory costs with techniques which are Lot for Lot (LFL), Least Unit Cost (LUC), Economic Order Quantity (EOQ), and Silver-Meal. Based on the calculation results, the four lot sizing techniques show that the LFL technique is the optimal technique compared to other techniques because it produces the minimum inventory cost of Rp566.015.685,05. Thus, the company can profit Rp13.295.563,75 compared to company policy.